Community Structure And Spatial Distribution of Mollusc in Southernt Part Of Leitimur Coastal Waters, Ambon City - yuliana natan; Juliaeta Adriana Bertha Mamesah; Tiara.Sanla Wattimury (Masyarakat Moluska Indonesia, 2023)
A resource that is often used by the coastal communities of South Leitimur, Ambon City to fulfill their daily needs is mollusks. The community has long been utilizing the resources of mollusks (Bivalves and Gastropods), which are taken at low tide (bameti) to meet their daily needs as a substitute for animal protein other than fish. The existence of protected and economically valuable species and then with continuous community activities, without being balanced with knowledge of the importance of resource conservation will result in the vulnerability of the existence of these mollusc resources to degradation. Information on the existence of molluscs and their distribution is needed to support fisheries management. The results showed that the coastal areas of South Leitimur District (Rutong, Hukurila and Leahari) had 94 species of mollusks, belonging to 2 classes, 9 orders, 33 families and 52 generas. The density values ranged from 0.003 ind / m2 - 4.99 ind / m2, while the frequency of presence values ranged from 0.003 - 0.5. The highest potential value of mollusk species is in the coastal of Negeri Rutong and the lowest is in the coastal of Negeri Hukurila. The diversity index value is moderate, with the evenesse index value that is classified as high. The dominance index value shows that there is no dominance of certain species. From various distribution patterns, as many as 103 species of molluscs were clumps, 40 species uniformly and two species randomly. Keywords: Community structure, spatial distribution, Mollusc, South Leitimur